Comparison of reversed-phase enantioselective HPLC methods for determining the enantiomeric purity of (S)-omeprazole in the presence of its related substances - Bruno Gallinella; Rosella Ferretti; Leo Zanitti; Isabella Sestili; Antonina Mosca; Roberto Cirilli (Elsevier, 2016)
A simple analytical high-performance liquid chromatography (HPLC) method was applied for the enantiomeric excess determination of esomeprazole ((S)-OME), the enantiopure active ingredient contained in drug products, in the presence of its potential organic impurities A-E. The enantioselective separation was accomplished on the immobilized-type Chiralpak ID-3 chiral stationary phase (CSP) under reversed-phase conditions. The results were evaluated and compared with those obtained by the official enantioselective method of European Pharmacopoeia used as the reference for checking the enantiomeric excess of (S)-OME. It has been established that the use of the Chiralpak ID-3 CSP allows the determination of the enantiomeric purity of (S)-OME without any interference coming from its chiral and achiral related substances. The analytical procedure of the drug regulatory agencies based on the AGP CSP suffered instead from poor specificity due to overlap of the peaks pertinent to the achiral impurity A and the chiral impurity (R)-OME (impurity F).